Electrocatalyst with RuFe nanoparticles cooperating with Ni3S2 and MXene heterojunction and application of electrocatalyst

The electrocatalyst that synergizes the heterojunction of RuFe nanoparticles with Ni3S2 and MXene is prepared by a one-step hydrothermal method. Combined with ultrasonic physics, the problems of high overpotential and instability of existing OER electrocatalysts are solved, and the effect of efficient OER reaction at lower overpotentials is achieved.

CN119685844AActive Publication Date: 2025-03-25HEBEI UNIV OF TECH +1

Patent Information

Application Number
CN202411875975.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The existing water-electrolytic oxygen reaction (OER) electrocatalysts have problems of high overpotential, instability and high cost, which limits their application in water-electrolytic hydrogen energy production.

Method used

The electrocatalyst in which RuFe nanoparticles synergizes the heterojunction of Ni3S2 and MXene is prepared by a one-step hydrothermal method. Nickel foam is used as a self-supporting framework to form a multi-layered structure electrocatalyst, and combined with ultrasonic physics to reduce overpotential and improve stability.

Benefits of technology

The OER reaction at a lower overpotential is achieved, reducing the overpotential of the electrocatalyst, improving its stability in long cycles, and reducing the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685844A_ABST
    Figure CN119685844A_ABST
Patent Text Reader

Abstract

The invention relates to an electrocatalyst with RuFe nanoparticles cooperating with Ni3S2 and MXene heterojunction and application of the electrocatalyst. The electrocatalyst can be expressed as RuFe / Ni3S2MX / NF. The self-supporting electrocatalyst with a composite structure is prepared in one step through a hydrothermal method, the catalyst has a multi-layer structure, NF serves as a self-supporting framework, the surface of the catalyst is of a heterojunction structure (granular Ni3S2 is wrapped with two-dimensional sheet structure Mxene) composed of Ni3S2 and MXene, and some RuFe nano-particle active sites exist on MXene, so that excellent OER performance is provided. The method is simple to operate, low in preparation and raw material cost and suitable for large-scale application. According to the invention, Ru and Fe are introduced and alloy is formed, so that the OER performance of the catalyst is improved in all directions, the Ru and Fe cooperate with each other to promote formation of RuFe alloy nanoparticles on the surface of a heterojunction, and active sites and specific surface area are increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalysis, and in particular relates to an electrocatalyst of RuFe nanoparticles in cooperation with Ni3S2 and MXene heterojunction and its application. Background Art

[0002] In today's world, with the continuous growth of energy demand and the increasing prominence of environmental problems, it is particularly important to develop efficient and sustainable energy conversion technologies. As a clean and renewable method for producing hydrogen energy, water electrolysis has received extensive research attention. Among them, the oxygen evolution reaction (OER) is a key half-reaction in the water electrolysis process, and its efficiency directly affects the energy conversion efficiency of the entire water electrolysis process. However, the kinetics of the OER reaction are slow and require high overpotentials to proceed, which greatly limits its practical application.

[0003] In recent years, NF-based self-supporting electrodes have received significant attention due to their inherent advantages such as stable spatial skeleton, binder-free, good electrical conductivity and cost-effectiveness. Transition metal chalcogenides represented by sulfides such as Ni3S2 have received extensive attention in recent years, but the instability of the materials and the relatively high overpotential need to be overcome. Existing NF-based heterojunction electrocatalysts generally require a high-temperature calcination process, which is relatively costly, and some of them need to be improved in stability during long-term cycle use. Summary of the invention

[0004] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to provide an electrocatalyst of RuFe nanoparticles in cooperation with Ni3S2 and MXene heterojunction and its application, the electrocatalyst can be expressed as RuFe / Ni3S2 MX / NF. A self-supporting electrocatalyst with a composite structure is prepared in one step by a hydrothermal method. The catalyst has a multilayer structure, NF as a self-supporting skeleton, and its surface is a heterojunction structure composed of Ni3S2 and MXene (a two-dimensional sheet structure MXene wraps granular Ni3S2). There are some RuFe nanoparticle active sites on MXene to provide excellent OER performance.

[0005] The technical solution adopted by the present invention to solve the technical problem is:

[0006] In the first aspect, the present invention provides an electrocatalyst of RuFe nanoparticles in cooperation with Ni3S2 and MXene heterojunction, wherein the electrocatalyst has a multilayer structure, with nickel foam NF as a self-supporting skeleton, a heterojunction structure composed of Ni3S2 and a two-dimensional flaky titanium carbon compound MXene formed on the surface of the nickel foam NF, and RuFe nanoparticles distributed on the heterojunction structure.

[0007] Furthermore, the RuFe nanoparticles are nanoparticles of RuFe alloy.

[0008] Furthermore, the preparation method of the electrocatalyst is:

[0009] S1. Using 1-3 mol / L sulfuric acid, water and ethanol to treat nickel foam in sequence, removing surface impurities and oxide layer before reaction treatment, and obtaining cleaned NF; the thickness of the nickel foam is less than 1 mm and greater than 0.2 mm;

[0010] S2, dispersing a suspension of a two-dimensional sheet-like titanium carbon compound MXene in a homogeneous solution containing an iron salt, a ruthenium salt, thiourea, and NH4F, adding CTAB after uniform dispersion, and stirring uniformly at room temperature to obtain a reaction solution; the metal molar ratio of the iron salt to the ruthenium salt is 0.8-1.2:1; the molar ratio of thiourea to NH4F is 2-3:1; the mass of CTAB added is 4-5 times the mass of MXene;

[0011] S3, immersing the cleaned NF into the reaction solution of step S2, and then performing a hydrothermal reaction at 100-140° C. in an autoclave for 8-16 hours;

[0012] S4, treating the solid material obtained in step S3 with an alcohol-water mixture by ultrasonic treatment for 5-20 min, and then vacuum drying to obtain the electrocatalyst.

[0013] Furthermore, the concentration of the suspension of the two-dimensional titanium carbon compound MXene is 5 to 10 mg / mL, and the MXene is Ti3C2T x , Ti3C2, T x Indicates a functional group.

[0014] Furthermore, the volume ratio of the reaction substances in the autoclave to the volume of the autoclave is 1:1.5-3.

[0015] Furthermore, the thickness of the nickel foam is 0.3-0.7 mm, and the size is 4 cm×10 cm; preferably 0.5 mm.

[0016] Furthermore, in step S3, the temperature of the hydrothermal reaction is 120° C. and the time is 12 hours.

[0017] In a second aspect, the present invention provides a use of the above-mentioned electrocatalyst in electrocatalytic oxygen evolution, the process comprising the following steps:

[0018] S100, cutting the electrocatalyst into pieces of 1 cm*1 cm in size, and ultrasonically treating the pieces for 5-15 min for later use;

[0019] S200, using the electrocatalyst as the working electrode, graphite as the counter electrode, and a saturated calomel electrode as the reference electrode, connected to an electrochemical workstation, and performing an electrocatalytic oxygen evolution reaction in a 1.0 M potassium hydroxide solution;

[0020] S300, placing the three-electrode system in a 40kHz ultrasonic cleaning machine, maintaining the temperature at 27±2°C, and adding an ultrasonic physical field during the electrocatalytic oxygen evolution reaction. The electrocatalytic oxygen evolution reaction process is carried out in the three-dimensional ultrasonic physical field formed by the ultrasonic cleaning machine to reduce the adhesion of oxygen evolution bubbles on the catalyst surface and promote the chemical reaction, thereby reducing the overpotential of the electrocatalyst at 10mA·cm -2 The overpotential under current density is reduced by 10mV;

[0021] S400, using chronopotentiometry at 10 mA cm -2 During a 20-hour long cycle at a current density of 4, the increase in overpotential relative to the initial value was controlled within 4 mV.

[0022] Further: in step S300, the ultrasonic frequency is 40kHz, and the ultrasonic power is 40-120W.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention synthesizes an oxygen evolution electrocatalyst having a heterojunction of RuFe nanoparticles and Ni3S2 and MXene by a one-step hydrothermal method. The method is simple to operate, has low preparation and raw material costs, and is suitable for large-scale application.

[0025] (2) The present invention synthesized a composite catalyst having a structure of RuFe nanoparticles, Ni3S2 and MXene heterojunction and NF substrate. The nanoparticles are RuFe alloys. This complex structure has abundant active areas, a larger active area and better electrochemical activity. The synergistic effect between the components further improves the material performance.

[0026] (3) In alkaline solution, the RuFe / Ni3S2 MX / NF electrocatalyst has a low overpotential as a working electrode, and its performance is better than most reported electrocatalysts. The electrocatalyst can be used as a working electrode at 10 mA cm -2 The overpotential is 262 mV at a current density of 1.38 Å, and the Tafel slope is 31 mV dec. -1 , the overpotential was reduced to 252mV under ultrasonic environment. And in the chronopotentiostatic test, at 10mA·cm -2Under the 20-hour long cycle at the current density, the overpotential only increases by less than 4mV, which has better stability. The present invention combines electrochemistry with ultrasound, and uses ultrasound to significantly improve the performance of RuFe / Ni3S2 MX / NF, so that the OER reaction can be carried out at a lower overpotential, and the catalyst can remain stable in an ultrasonic environment.

[0027] (4) The introduction of Ru and Fe and the formation of alloys in the present invention comprehensively improve the OER performance of the catalyst. Thiourea serves as the sulfur source of Ni3S2, and the weak reducing property of NH4F can reduce Ru salts and iron salts. The positive charge of CTAB causes the negatively charged MXene to precipitate on the outside of NF. The synergistic effect of the above factors promotes the formation of RuFe alloy nanoparticles on the heterojunction surface, increasing the active sites and specific surface area. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The present invention will be described in detail below with reference to the accompanying drawings and in combination with examples, and the advantages and implementation methods of the present invention will become more obvious. The contents shown in the accompanying drawings are only used to explain the present invention and do not constitute any limitation to the present invention in any sense. In the accompanying drawings:

[0029] Figure 1 These are the SEM and TEM images of RuFe / Ni3S2 MX / NF of the present invention.

[0030] Figure 2 The XRD diagrams of RuFe / Ni3S2 MX / NF in the present invention and the comparative example product.

[0031] Figure 3 This is the XPS graph of RuFe / Ni3S2 MX / NF of the present invention.

[0032] Figure 4 This is the BET diagram of RuFe / Ni3S2MX / NF in the embodiment of the present invention.

[0033] Figure 5 4 is a comparison chart of the electrochemical properties of different samples in the embodiments of the present invention. DETAILED DESCRIPTION

[0034] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the best embodiment.

[0035] The present invention discloses an electrocatalyst of a heterojunction of RuFe nanoparticles in cooperation with Ni3S2 and MXene (denoted as RuFe / MXene / NF electrocatalyst). The electrocatalyst has a multilayer structure, with nickel foam NF as a self-supporting skeleton, a heterojunction structure composed of Ni3S2 and a two-dimensional flaky titanium carbon compound MXene formed on the surface of the nickel foam NF, and RuFe nanoparticles distributed on the heterojunction structure.

[0036] The preparation method of the electrocatalyst is:

[0037] S1. Using 1-3 mol / L sulfuric acid, water and ethanol to treat nickel foam in sequence, removing surface impurities and oxide layer before reaction treatment, and obtaining cleaned NF; the thickness of the nickel foam is less than 1 mm and greater than 0.2 mm;

[0038] S2, dispersing a suspension of a two-dimensional sheet-like titanium carbon compound MXene in a homogeneous solution containing an iron salt, a ruthenium salt, thiourea, and NH4F, adding CTAB after uniform dispersion, and stirring uniformly at room temperature to obtain a reaction solution; the metal molar ratio of the iron salt to the ruthenium salt is 0.8-1.2:1; the molar ratio of thiourea to NH4F is 2-3:1; the mass of CTAB added is 4-5 times the mass of MXene;

[0039] S3, immersing the cleaned NF into the reaction solution of step S2, and then performing a hydrothermal reaction at 100-140° C. in an autoclave for 8-16 hours;

[0040] S4, treating the solid material obtained in step S3 with an alcohol-water mixture by ultrasonic treatment for 5-20 min, and then vacuum drying to obtain the electrocatalyst.

[0041] The thickness of the nickel foam used in the present invention is between 0.2-1 mm, preferably 0.3-0.7 mm.

[0042] For further optimization, nickel foam with a thickness of 0.5 mm was selected in S1 and treated three times in sequence with 2 mol / L sulfuric acid, water, and ethanol.

[0043] Further optimization, S2 was added with 6 mL of 10 mg / mL Ti3C2T x The suspension was dispersed in 44 mL of a homogeneous solution containing 1 mmol FeCl3·6H2O, 1 mmol RuCl3·3H2O, 5 mmol thiourea, and 2.5 mmol NH4F, and then 25 mg CTAB was introduced under magnetic stirring at room temperature for 30 min.

[0044] After further optimization, the temperature of S3 hydrothermal reaction was 120°C and the time was 12 hours.

[0045] After further optimization, the catalyst in S4 was ultrasonically treated for 10 min and dried in a vacuum drying oven for 12 h.

[0046] The application of the RuFe / MXene / NF electrocatalyst in the electrocatalytic oxygen evolution reaction of the present invention comprises the following specific steps:

[0047] S100, cutting the electrocatalyst into pieces of 1 cm*1 cm in size, and ultrasonically treating the pieces for 5-15 min for later use;

[0048] S200, using the electrocatalyst as the working electrode, graphite as the counter electrode, and a saturated calomel electrode as the reference electrode, connected to an electrochemical workstation, and performing an electrocatalytic oxygen evolution reaction in a 1.0 M potassium hydroxide solution;

[0049] S300, placing the three-electrode system in a 40kHz ultrasonic cleaning machine, maintaining the temperature at 27±2°C, and adding an ultrasonic physical field during the electrocatalytic oxygen evolution reaction. The electrocatalytic oxygen evolution reaction process is carried out in the three-dimensional ultrasonic physical field formed by the ultrasonic cleaning machine to reduce the adhesion of oxygen evolution bubbles on the catalyst surface and promote the chemical reaction, thereby reducing the overpotential of the electrocatalyst at 10mA·cm -2 The overpotential under current density is reduced by 10mV;

[0050] S400, using chronopotentiometry in a non-ultrasonic environment, at 10 mA cm -2 During a 20-hour long cycle at a current density of 4, the increase in overpotential relative to the initial value was controlled within 4 mV.

[0051] The present invention uses an ultrasonic cleaning machine in conjunction with the electrocatalytic oxygen evolution reaction process, so that the entire reaction process is completed in a three-dimensional ultrasonic atmosphere. During this process, the electrocatalyst can exist stably without peeling or breaking, and the overpotential is further reduced under the same conditions. The ultrasonic power is 40W-120W and the frequency is 40kHz.

[0052] Example 1

[0053] The preparation process of the RuFe nanoparticles in this embodiment in cooperation with the Ni3S2 and MXene heterojunction electrocatalyst is as follows:

[0054] First, 0.5 mm thick nickel foam (NF) was treated with 1-3 mol / L sulfuric acid, water, and ethanol in sequence to remove surface impurities and oxide layers before the reaction treatment. The size of the nickel foam was 4 cm×10 cm.

[0055] 6 mL of 10 mg / mL Ti3C2T xThe suspension was dispersed in 44 mL of a homogeneous solution containing 1 mmol FeCl3·6H2O, 1 mmol RuCl3·3H2O, 5 mmol thiourea, and 2.5 mmol NH4F, and then 0.025 g CTAB was introduced under magnetic stirring at room temperature for 30 min to obtain a reaction solution.

[0056] The cleaned NFs were immersed in the obtained reaction solution and transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction at 120 °C for 12 h.

[0057] The solid material obtained by hydrothermal treatment was ultrasonically treated with a mixture of ethanol and water in a volume ratio of 1:1 for 10 minutes to remove surface impurities, and then placed in a vacuum drying oven and dried at 60°C to obtain a RuFe / Ni3S2MX / NF electrocatalyst.

[0058] The electrocatalysts were tested by SEM, TEM, XRP and adsorption performance:

[0059] Figure 1 (a) and (b) show the morphology of RuFe / Ni3S2 MX / NF electrocatalyst under scanning electron microscopy. There are many protrusions on the surface of the NF skeleton wrapped by MXene wrinkles. This is the relationship between Ni3S2 and Ti3C2T x In the hydrothermal reaction system, the positively charged CTAB can act as a chelating component to promote the negatively charged Ti3C2T x Deposition on the outside of NF to form Ni3S2 and Ti3C2T x of heterojunction. Figure 1 (c) is a TEM image of RuFe / Ni3S2 MX / NF. It can be observed that RuFe nanoparticles are dispersed on the MXene carrier. The lattice fringes of RuFe nanoparticles were measured and it was found that the interplanar spacing was 0.224nm, slightly smaller than Ru(100), forming a RuFe alloy. According to the analysis of diffraction SAED and HRTEM of the selected area (selecting the solid sample area and then shooting, in which the diffraction patterns and diffraction rings of these substances exist), it can be known that Ti3C2T x , Ni3S2 and RuFe coexist in this region.

[0060] The surface chemical properties of RuFe / Ni3S2 MX / NF were characterized by XPS measurement. The XPS spectrum shows the coexistence of Ru, Fe, Ni and S elements in RuFe / Ni3S2 MX / NF electrocatalyst. The spectrum of Ni 2p is shown in Figure 2. Figure 3 As shown in (a). The peaks at 873.4eV and 855.7eV are Ni 2p 1 / 2 and Ni 2p 3 / 2 , which is attributed to Ni2+ The peaks at 861.3 eV and 879.2 eV were identified as satellite peaks of Ni. Figure 3 As shown in (b), the fitting signals of the binding energy of metal Fe at 706.8eV, 710.1eV, and 721.9eV are the surface oxidized Fe 2+ The fitting signals at 712.9 eV and 726.1 eV are Fe 3+ The spectrum of Ru 3p is Figure 3 As shown in (c), the peaks at 462.1eV and 484.5eV are respectively related to Ru 3p 3 / 2 and Ru 3p 1 / 2 This is attributed to Ru 0 , the peaks at 465.0 eV and 487.0 eV correspond to the Ru 3p 3 / 2 and Ru 3p 1 / 2 Related, attributed to Ru 2+ ;exist Figure 3 The peaks at 163.15 eV and 151.9 eV in the S2p spectrum of (d) were identified as S2p 1 / 2 and S2p 3 / 2 , while the peak at 168.5eV is attributed to the highly oxidized state of sulfate substances. The existence of Ru / Fe in 0 valence state indicates that they exist in the form of alloys, and Ni only has 2+, indicating that it exists in the form of Ni3S2.

[0061] The N2 adsorption-desorption curve of RuFe / Ni3S2 MX / NF is shown in Figure 4 As shown, it shows a typical mesoporous structure. The specific surface area of ​​RuFe / Ni3S2MX / NF is 3.792m 2 / g, which is larger than the specific surface area of ​​NF (3.225m 2 / g), which indicates that the Ni3S2 / MXene heterojunction and RuFe nanoparticles (NPs) provide more active areas for RuFe / Ni3S2 MX / NF.

[0062] The electrocatalyst of the embodiment was tested for electrocatalytic oxygen evolution reaction: 1.0M potassium hydroxide solution was prepared as the electrocatalytic electrolyte, argon gas was introduced to drive away the air, the prepared electrocatalyst was used as the working electrode, graphite was used as the counter electrode, and a saturated calomel electrode was used as the reference electrode. The electrochemical workstation was connected to carry out electrocatalytic hydrogen evolution reaction in the electrolyte.

[0063] Without adding ultrasonic environment during the electrocatalytic hydrogen evolution reaction, the electrocatalyst -2 The overpotential is 262 mV and the Tafel slope is 31 mV dec. -1After adding the three-dimensional ultrasound environment, the overpotential of the electrocatalyst was reduced to 252 mV.

[0064] Chronopotentiometry was used at 10 mA cm -2 During a 20-hour cycle at a current density of 1.5 Å, the overpotential increase relative to the initial value was controlled within 4 mV (see Figure 5 As shown in Figure (c)). It can be seen from the figure that the long-term cycle stability of the RuFe nanoparticles introduced in the present invention is obviously the best.

[0065] The electrocatalytic activity of the OER was evaluated by linear sweep voltammetry (LSV). Figure 5 In figure a, the dotted line is with ultrasound, and the solid line is without ultrasound. b is the corresponding Tafel diagram; c is the chronopotentiometry; d is the LSV of other comparison samples. The LSV test was performed at an extremely low potential scan rate (2 mV s -1 ) to ensure that steady-state conditions are achieved at each potential value. After applying ultrasound, the performance of different catalysts is improved. RuFe / Ni3S2 MX / NF, Ru / Ni3S2 MX / NF, Fe / Ni3S2MX / NF, and NF are significantly improved at overpotential (10 mA cm -2 ) were reduced by 10mV, 10mV, 11mV and 9mV respectively, and the addition of ultrasound made the performance of the catalyst in the entire test range to be stably improved.

[0066] Comparative Example 1

[0067] The difference between this comparative example and Example 1 is that only RuCl3·3H2O is added to the homogeneous solution, but FeCl3·6H2O is not added.

[0068] Electrocatalytic oxygen evolution reaction application test: The electrocatalyst of this comparative example was tested at a current density of 10 mA cm -2 The overpotential is 309 mV and the Tafel slope is 41 mV dec. -1 After adding ultrasound, the overpotential of this electrocatalyst decreased to 299 mV.

[0069] At 10 mA cm -2 The overpotential increased by 8 mV during 20 h long cycling at the same current density.

[0070] Comparative Example 2

[0071] The difference between this comparative example and Example 1 is that only FeCl3·6H2O is added to the homogeneous solution, but RuCl3·3H2O is not added.

[0072] Electrocatalytic oxygen evolution reaction application test: at a current density of 10 mA cm -2The overpotential is 317 mV and the Tafel slope is 79 mV dec. -1 The lower the Tafel slope, the better the catalyst performance, which is only related to the performance of the catalyst itself. After adding ultrasound, the overpotential of the electrocatalyst dropped to 306mV. Chronopotentiometry at 10mA·cm -2 The overpotential increased by 47 mV during 20 h long cycling at the same current density.

[0073] Comparative Example 3 (containing only Ni3S2 and Ti3C2T x Heterojunction

[0074] The difference between this comparative example and Example 1 is that FeCl3·6H2O and RuCl3·3H2O are not added to the homogeneous solution.

[0075] Electrocatalytic oxygen evolution reaction application test: The material has a current density of 10 mA cm -2 The overpotential is 340mV.

[0076] Comparative Example 4

[0077] The difference between this comparative example and Example 1 is that no Ti3C2T x .

[0078] First, 0.5 mm thick nickel foam (NF) was treated with 1-3 mol / L sulfuric acid, water, and ethanol in sequence to remove surface impurities and oxide layers before the reaction. 50 mL of a homogeneous solution containing 1 mmol FeCl3·6H2O, 1 mmol RuCl3·3H2O, 5 mmol thiourea, and 2.5 mmol NH4F was added, and then 0.025 g CTAB was introduced into the room temperature magnetic stirring for 30 min. The cleaned NF was immersed in the reaction solution and transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction at 120 ° C for 12 hours. The catalyst obtained by hydrothermal treatment was ultrasonically treated with a mixture of ethanol and water with a volume ratio of 1:1 for 10 minutes to remove surface impurities, and then placed in a vacuum drying oven at 60 ° C to dry to obtain an electrocatalyst.

[0079] Electrocatalytic oxygen evolution reaction application test: at a current density of 10 mA cm -2 The overpotential is 276mV.

[0080] By comparing Example 1 with Comparative Examples 1-4, it can be found that the simultaneous presence of iron and ruthenium can significantly reduce the overpotential, and its effect is greater than that of the heterojunction. Under the same conditions, the overpotential of commercial ruthenium oxide tested at a current density of 10mA cm-2 is 351mV, while that of Ni3S2 and Ti3C2T xThe performance of the heterojunction itself is already better than that of commercial RuO2, and the synergy of RuFe nanoparticles further improves the performance of the electrocatalyst.

[0081] Comparative Example 5

[0082] The difference between this comparative example and Example 1 is that the substrate is carbon cloth and does not contain Ni3S2 and Ti3C2T x of heterojunction.

[0083] First, 0.5 mm thick carbon cloth (CC) was treated with 1-3 mol / L sulfuric acid, water, and ethanol in sequence to remove surface impurities and oxide layers before reaction. 50 mL of a homogeneous solution containing 1 mmol FeCl3·6H2O, 1 mmol RuCl3·3H2O, 5 mmol thiourea, and 2.5 mmol NH4F was added, and then 0.025 g CTAB was introduced into the room temperature magnetic stirring for 30 min. The cleaned CC was immersed in the obtained solution and transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction at 120 ° C for 12 hours. The catalyst obtained by hydrothermal reaction was washed with a mixture of ethanol and water in a volume ratio of 1:1 to remove surface impurities, and then placed in a vacuum drying oven and dried at 60 ° C to obtain an electrocatalyst.

[0084] Electrocatalytic oxygen evolution reaction application test: The material has a current density of 10 mA cm -2 The overpotential is 346mV.

[0085] By comparing Comparative Examples 5 and 4, it can be found that the foamed nickel matrix also has a significant promoting effect on the reduction of overpotential.

[0086] Figure 2 The XRD test comparison results of three samples, RuFe / Ni3S2 MX / NF, Ru / Ni3S2 MX / NF, and Fe / Ni3S2 MX / NF, are shown. Due to the extremely strong diffraction peak of NF and the extremely low content of other substances, the XRD results of Ti3C2T x The signal of MXene-RuFe is invisible, and only Ni3S2 and Ni peaks can be observed, indicating that the content of these substances is extremely low. An extremely low content of active substances can greatly improve the performance of the catalyst, which means that the catalyst cost is also low.

[0087] Example 2

[0088] In this embodiment, based on Example 1, the thickness of the nickel foam is changed to 0.2 mm, 0.4 mm, 0.8 mm, and 1 mm, respectively, and its electrocatalytic oxygen evolution reaction performance is tested. When the thickness of the nickel foam is less than 0.2 mm, the nickel skeleton becomes fragile after the reaction, and is broken after ultrasonic treatment and the performance is not good; and the nickel foam with a thickness of 1 mm will be peeled into two layers after ultrasound, affecting its catalytic performance.

[0089] Example 3

[0090] In this embodiment, RuFe / Ni3S2 MX / NF electrocatalyst is prepared, which is a composite self-supporting electrode of RuFe nanoparticles cooperating with Ni3S2 and MXene heterojunction. The thickness of nickel foam is 0.4mm, the reaction liquid is a gray solution (mainly showing the color of MXene, MXene solution is gray), the metal molar ratio of iron salt to ruthenium salt is 0.8:1 or 1.2:1, the total reaction liquid volume is 60mL, the reactor volume is 100mL, and during the hydrothermal synthesis process, the RuFe nanoparticles cooperating with Ni3S2 and MXene heterojunction grown in situ on nickel foam have higher active area and intrinsic activity, higher stability, and small overpotential change, excellent cycle durability, and can stably exist in a three-dimensional ultrasonic environment.

[0091] The noble metal Ru in the present invention can effectively reduce the overpotential of the reaction, increase the reaction rate, and make the water decomposition process more efficient. In addition, Ru can effectively promote the reaction path of OER, reduce the energy barrier of the reaction, show excellent chemical stability, and can also produce synergistic effects with Fe metal, which is more economical. The prepared catalyst can stably exist in an ultrasonic environment. Ultrasound accompanies the entire reaction process in the reaction application, which can promote the formation and release of bubbles and reduce the adhesion of bubbles on the catalyst surface; it can also induce sonochemical reactions, resulting in transient phenomena of local high temperature and high pressure, promoting the occurrence of chemical reactions, and avoiding the problem of significant adverse effects on the performance of the catalyst during the electrocatalytic process due to the generation and existence of bubbles attached to the catalyst surface, forming a physical barrier, hindering the contact between the reactants and the catalyst.

[0092] The present invention uses RuFe nanoparticles, Ni3S2 and Ti3C2T x The multilayer structure consists of three major elements: heterojunction and NF matrix. The electrocatalyst can achieve stable self-supporting effect. On the premise of ensuring the active sites on the catalyst, it can remain stable under ultrasonic conditions. The electrocatalytic oxygen evolution reaction process is accompanied by a three-dimensional ultrasonic environment, which enables the reaction to be coupled with ultrasound, which can further reduce the overpotential and has a significant effect.

[0093] The present invention can achieve a lower overpotential at the lowest cost under one-step hydrothermal conditions without the need for high-temperature calcination, has a significant effect, and is conducive to promotion and application and improved economic benefits.

[0094] The embodiments of the present invention are described in detail above, but the contents are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. An electrocatalyst of RuFe nanoparticles synergistic with Ni3S2 and MXene heterojunction, characterized in that: The electrocatalyst has a multilayer structure, with nickel foam NF as a self-supporting skeleton, a heterojunction structure composed of Ni3S2 and a two-dimensional sheet-like titanium carbon compound MXene formed on the surface of the nickel foam NF, and RuFe nanoparticles distributed on the heterojunction structure.

2. The electrocatalyst according to claim 1, characterized in that The RuFe nanoparticles are nanoparticles of RuFe alloy.

3. The electrocatalyst according to claim 1, characterized in that The preparation method of the electrocatalyst is: S1. Using 1-3 mol / L sulfuric acid, water and ethanol to treat nickel foam in sequence, removing surface impurities and oxide layer before reaction treatment, and obtaining cleaned NF; the thickness of the nickel foam is less than 1 mm and greater than 0.2 mm; S2, dispersing a suspension of a two-dimensional sheet-like titanium carbon compound MXene in a homogeneous solution containing an iron salt, a ruthenium salt, thiourea, and NH4F, adding CTAB after uniform dispersion, and stirring uniformly at room temperature to obtain a reaction solution; the metal molar ratio of the iron salt to the ruthenium salt is 0.8-1.2:1; the molar ratio of thiourea to NH4F is 2-3:1; the mass of CTAB added is 4-5 times the mass of MXene; S3, immersing the cleaned NF into the reaction solution of step S2, and then performing a hydrothermal reaction at 100-140° C. in an autoclave for 8-16 hours; S4, treating the solid material obtained in step S3 with an alcohol-water mixture by ultrasonic treatment for 5-20 min, and then vacuum drying to obtain the electrocatalyst.

4. The electrocatalyst according to claim 3, characterized in that The concentration of the suspension of the two-dimensional titanium carbon compound MXene is 5 to 10 mg / mL, and the MXene is Ti3C2T x , Ti3C2, T x Indicates a functional group.

5. The electrocatalyst according to claim 3, characterized in that The volume ratio of the reaction substances in the autoclave to the volume of the autoclave is 1:1.5-3.

6. The electrocatalyst according to claim 3, characterized in that The thickness of the nickel foam is 0.3-0.7 mm, and the size is 4 cm×10 cm, preferably 0.5 mm.

7. The electrocatalyst according to claim 3, characterized in that In step S3, the temperature of the hydrothermal reaction is 120° C. and the time is 12 hours.

8. Use of the electrocatalyst according to any one of claims 1 to 7 in electrocatalytic oxygen evolution, characterized in that: The application process in electrocatalytic oxygen evolution includes the following steps: S100, cutting the electrocatalyst into pieces of 1 cm*1 cm in size, and ultrasonically treating the pieces for 5-15 min for later use; S200, using the electrocatalyst as the working electrode, graphite as the counter electrode, and a saturated calomel electrode as the reference electrode, connected to an electrochemical workstation, and performing an electrocatalytic oxygen evolution reaction in a 1.0 M potassium hydroxide solution; S300, placing the three-electrode system in a 40kHz ultrasonic cleaning machine, maintaining the temperature at 27±2°C, and adding an ultrasonic physical field during the electrocatalytic oxygen evolution reaction. The electrocatalytic oxygen evolution reaction process is carried out in the three-dimensional ultrasonic physical field formed by the ultrasonic cleaning machine to reduce the adhesion of oxygen evolution bubbles on the catalyst surface and promote the chemical reaction, thereby reducing the overpotential of the electrocatalyst at 10mA·cm -2 The overpotential under current density is reduced by 10mV; S400, using chronopotentiometry at 10 mA cm -2 During a 20-hour long cycle at a current density of 4, the increase in overpotential relative to the initial value was controlled within 4 mV.

9. The use according to claim 8, characterized in that: In step S300, the ultrasonic frequency is 40 kHz, and the ultrasonic power is 40-120 W.

Citation Information

Patent Citations

  • Preparation method of bimetallic sulfide / MXene complex for oxygen evolution by electrolyzing water

    CN114196988A

  • Ruthenium nano-cluster / trinickel disulfide heterojunction composite material as well as preparation method and application thereof

    CN119571381A

Cited By

  • Hydrogen evolution electrocatalyst, preparation method therefor, and use thereof

    WO2026040290A1